The clinical efficacy of novel semirigid ureteroscopy with a vacuum suction device for treatment of >10 mm upper ureteral stones and impacted calculus: implications for clinical practice - Lai, Longhui; Zhang, Yuanfeng; Wang, Yingru; Yang, Enguang; Fan, Guangrui; Chen, Chaohu; Yao, Kang; Zhang, Wenzhao; Liu, Yongfei; Zhu, Kai; Ding, Meixuan; Xing, Jinchun; et al. (Frontiers in Surgery, 2026)
ObjectiveThe novel semirigid ureteroscopy with a vacuum suction device has been increasing in the treatment of urinary stones recently. This study aimed to evaluate its clinical efficacy for treating >10 mm upper ureteral stones and impacted calculus and to further assess the efficacy by using a vacuum suction device during lithotripsy procedures.Patients and methodsThis study included 156 patients with >10 mm upper ureteral calculi who underwent laser lithotripsy under the novel semirigid ureteroscopy with a vacuum suction device. The vacuum suction device and the end of the ureteral access sheath (UAS) were joined together to create a closed circulation working channel between the former and the collection system. This circulation working channel allows the operator to suction stone fragments out of the body during lithotripsy. Based on impacted and non-impacted upper ureteral stones, subgroup analysis was performed.ResultsOf the 156 patients, 150 underwent successful phase I ureteral sheath placement and lithotripsy. 6 patients were unsuccessfully placed for UAS because of upper ureteral stenosis, but all of them received indwelling Double-J tubes for one month and then underwent successful second-stage lithotripsy. The average operative time was 43.8 ± 25.7 min. The stone-free rate (SFR) was 57.7% (90/156) at 1 day postoperatively, and 87.8% (137/156) at 1 month postoperatively. The rate of complications was 9.0% (14/156). In subgroup analysis, for the impacted stone group, the average operative time was 48.0 ± 29.3 min. The SFR was 54.8% (46/84) at 1 day postoperatively, and 88.1% (74/84) at 1 month postoperatively. The rate of complications was 10.7% (9/84).ConclusionFor the treatment of >10 mm upper ureteral stones and impacted calculus, the novel semirigid ureteroscopy with a vacuum suction device is safe and effective. During the lithotripsy procedure, the use of a vacuum suction device has the potential to improve stone removal efficiency. However, due to the critical limitation of the lack of integrated pressure monitoring and control devices, potential complications caused by negative pressure suction and perfusion flow imbalance should be watched out for.